1990
DOI: 10.1021/jm00169a019
|View full text |Cite
|
Sign up to set email alerts
|

Conformational restriction of angiotensin II: cyclic analogs having high potency

Abstract: Cyclic analogues of angiotensin II (AII) were synthesized by connecting the side chains of residues 3 and 5 via a disulfide bridge. Appropriate conformational constraints afforded an analogue, [Hcy3,5]AII, having high contractile activity (pD2 = 8.48 vs 8.81 for AII) and excellent binding affinity (IC50 = 2.1 nM vs 2.2 nM for AII). This type of cyclization was also used to prepare a highly potent AII antagonist, [Sar1,Hcy3,5,Ile8]AII (pA2 = 9.09 vs 9.17 for [Sar1, Ile8]AII; IC50 = 0.9 nM vs 1.9 nM for [Sar1,Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1
5

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 12 publications
1
56
1
5
Order By: Relevance
“…Contractile response assays showed that all the analogs presented insignificant contractile activity by their interaction with the AT 1 receptor. These results are in opposition to those obtained previously by Spear et al (27) in which some disulfide-bridge-containing analogs showed pressor activity. However, according to Regoli et al (46), the substitution of certain residues in the primary sequence of AII caused a decrease in the pressor activity, as was observed in this work.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contractile response assays showed that all the analogs presented insignificant contractile activity by their interaction with the AT 1 receptor. These results are in opposition to those obtained previously by Spear et al (27) in which some disulfide-bridge-containing analogs showed pressor activity. However, according to Regoli et al (46), the substitution of certain residues in the primary sequence of AII caused a decrease in the pressor activity, as was observed in this work.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are in opposition to those obtained previously by Spear et al . in which some disulfide‐bridge‐containing analogs showed pressor activity. However, according to Regoli et al .…”
Section: Discussionmentioning
confidence: 99%
“…This cyclisation scheme through the oxidation of the sulfhydryl group has the advantage of limiting the changes in physiochemical properties and bulkiness of the cycle. Note that previous work has shown that cyclisation through these side-chains of AngII led to compounds that can still bind and elicit Gq/11 activation [20,21]. However, the impact on the biased signaling has not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The crude deprotected peptides were precipitated with anhydrous diethyl ether, filtered from the ether-soluble products, extracted from the resin with 60% acetonitrile (ACN) in water, and lyophilized. The disulfide bridges were formed by first solubilizing the crude peptides (1 g L À1 ) in an 80% acetic acid solution containing 0.04 mol L À1 iodine [21]. After 40 min the reaction was extracted with water and diethyl ether.…”
Section: Peptide Synthesis Purification and Characterizationmentioning
confidence: 99%